Public Communication on Science and Technology - Lamichhane, Shobha Kanta (Himalayan Physics, 2015)
'Comfort living' is the indicator of the development of a nation. Comfortable and prosperous living cannot be imagined without proper use of science and technology (S&T). And, technology cannot survive without a strong foundation of development in science. S&T research in nanotechnology promises breakthrough in medicine and healthcare, energy and environment, nanoelectronics and national security etc. It is widely felt that nanotechnology will be the next industrial revolution. We Nepalese people are unfortunate since we don't have proper national planning in S&T and let it be keep into least priority. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014)Page: 12-16